Exploring EFL Teachers’ Perceptions of Action Research in Two Public Universities in Saudi Arabia - Moahmmed Alwafi, Maram; Alkubaidi, Miriam (International Journal of English Language Education, 2024)
This study aimed to examine the knowledge, practice, and obstacles of action research (AR) among English as a foreign language (EFL) teachers at two public universities in Saudi Arabia. To achieve this aim, the study employed a quantitative research design using an online questionnaire. The data was collected from 96 EFL teachers working at English language institutes of two public universities in Saudi Arabia. The findings of the study revealed that most EFL teachers were familiar with AR, and the knowledge of AR was widespread among the participants. On the other hand, the findings showed deficiency in the practice of AR among EFL teachers. The findings also revealed that time and lack of training in AR were the most significant obstacles that hindered EFL teachers from conducting AR. Based on these findings, the study offered practical implications and recommendations for promoting the practice of AR among EFL teachers.